Investigation of the flow between a PV panel and building’s outer skin comprising a naturally ventilated BIPV system - Agathokleous, Rafaela; Kalogirou, Soteris A. (My University, 2019)
The installation of BIPV systems should be able to circulate cooling air at the back side of the PV panels in order to maintain high electrical conversion efficiency of the PV panels and avoid building overheating. This paper is focused on the understanding of the airflow between the building’s façade and the PV panel in naturally ventilated Building Integrated Photovoltaic (BIPV) panels. Flow visualisation measurements, hot wire anemometer measurements as well as temperature measurements were performed. These were performed in laboratory controlled environmental conditions under constant artificial solar radiation. These results are supported also with CFD simulation results. It is shown that the openings of the duct have an important role on the thermal behaviour of the system, and buoyancy effect resulted to velocities of 0.3 m/s. The optimum configuration is finally tested at building level to a demonstration building at Mons, Belgium, with very satisfactory results.
Keywords: BIPV system; Airflow; Building façade